Miniaturized Skin-Integrated Electronics in Real Time for Virtual Assistance - A Review - Senthilkumar, T.; Thangavelu, Anuradha (Journal of Electronics and Informatics, 2022)
The skin acts as a conduit between the brain and the outside environment. The information it receives, such as a touch on the shoulder or the heat from a fire, is processed and used to choose an appropriate response by the brain. A skin functionality may be achieved by incorporating sensors onto bionic skins that are on par with the sensitivity of biological skins. However, doing so is not simple. Recent developments in physiological sensing, sensory perception, and virtual and augmented reality are discussed, as are other intelligent uses of skin-integrated electronics. These skin-integrated systems are advancing the materials and structural designs necessary for the next generation of electronic eyes, ears, and skin. Future progress in this area of study will be aided by interdisciplinary exploration into fields such as materials science, electrical engineering, mechanics, and biomedical engineering.